We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
203
1
avatar

f(x)=(2x+3)/(x-4)

work out f to the power of -1 (x)

 Mar 1, 2019
 #1
avatar+19690 
+1

f^-1 is the inverse of f(x)

 

(2x+3)/(x-4)   = y       solve for 'x'

first do the division on the left to get

2+ 11/(x-4) = y          subtract 2 from each side

11/(x-4) = y-2          re-arrange

11/(y-2) = x-4          add 4 to both sides

11/(y-2) + 4 = x       change y to x and x to y

11/(x-2) +4 = y        simplify

 

(11 + 4x -8 )/(x-2) = y

(4x+3) / (x-2) = f^-1

 Mar 1, 2019

4 Online Users

avatar